The Hubungan Penyakit Jantung Bawaan (PJB) Dengan Status Gizi Pada Balita: Literature Review: Hubungan Penyakit Jantung Bawaan (PJB) Dengan Status Gizi Pada Balita: Literature Review - Pertiwi, Nabila Rahma; Berawi, Khairun Nisa (Medula, 2025)
Congenital Heart Disease (CHD) is a heart condition present at birth, with a global incidence of 9.4 cases per 1,000 live births, and in Indonesia, around 8 cases per 1,000 births. Children with CHD, especially those experiencing malnutrition, are at high risk of growth disorders due to energy imbalance and nutrient deficiencies. Studies on infants with cyanotic and acyanotic CHD show a significant relationship between the type of CHD and the child’s nutritional status. Cyanotic CHD has a greater impact on growth disorders compared to acyanotic CHD, with infants with cyanotic CHD having lower weight and height. The research also indicates that infants with cyanotic CHD have a higher risk of malnutrition due to difficulty meeting their energy needs through food intake. Malnutrition in infants with CHD can be caused by insufficient food intake, inefficient nutrient absorption, and increased energy demands due to the heart working harder. Hypoxemia in cyanotic CHD leads to decreased appetite, increased workload on the heart and lungs, and inefficient thermoregulation, ultimately increasing calorie needs. Additionally, hypoxemia causes changes in body tissue, such as a reduction in fat cells, leading to chronic malnutrition. Increased blood viscosity due to erythrocytosis impedes blood flow and oxygen distribution, worsening the energy imbalance that significantly affects the growth of infants.